Land fragmentation and green farming: livelihood strategies and resource endowment in sustainable agriculture - Das, Ghansham; Lufeng, Li; Xiaohong, Yang; Hailian, Zhang; Tunio, Raza Ali; Khan, Nawab (Frontiers in Sustainable Food Systems, 2025)
Land fragmentation poses a significant barrier to sustainable agricultural development by influencing farmers’ willingness and ability to adopt green production practices. This study aims to examine how land fragmentation affects such adoption, with particular attention to the mediating role of livelihood strategies and the moderating effect of resource endowments. The study utilizes survey data from 650 farmers in the provinces of Khyber Pakhtunkhwa and Balochistan, Pakistan. To analyze the relationships, we employed ordinary least squares (OLS) regression, threshold effect models, as well as mediation and moderation effect models. The analysis reveals that land fragmentation generally constrains the adoption of green production practices. However, the relationship is non-linear, exhibiting an inverted U-shape: moderate fragmentation can initially facilitate green adoption, while excessive fragmentation hinders it. Furthermore, livelihood strategies mediate this relationship, and resource endowments play a significant positive moderating role. The effects also vary across farmer generations, indicating heterogeneous behavioral responses. The findings underscore the complex and dynamic influence of land fragmentation on green agricultural practices. Policymakers should focus on resource integration, land-use optimization, and support for diversified livelihood strategies to promote sustainable agricultural development.